Compound-Specific Nitrogen Isotope Analysis of Amino Acids in Eye Lenses as a New Tool to Reconstruct the Geographic and Trophic Histories of Fish - Harada, Yota; Ito, Shin-ichi; Ogawa, Nanako O.; Yoshikawa, Chisato; Ishikawa, Naoto F.; Yoneda, Michio; Ohkouchi, Naohiko (Frontiers in Marine Science, 2022)
Fish migration has always played an essential role in marine conservation and fisheries management. However, migration patterns are changing globally alongside changing ocean conditions. This affects the spatial scale of required governance and, consequently, our food supply. Technological advances in the bio-tracer approach using isotopes would make it possible to monitor fish migration differently from the conventional bio-logging method. Eye lenses of fish are incrementally grown and metabolically inert. Therefore, stable isotope analysis of eye lenses can reconstruct the geographic and trophic histories of fish. However, it is difficult to distinguish between the two pieces of information: migration and changing trophic relationships with the conventional bulk stable isotope approach. In this study, we measured the nitrogen isotope ratios of individual amino acids in eye lenses of chub mackerel (n = 3) from the western North Pacific to test whether the two pieces of information could be distinguished. A maximum of 34 growth layers was obtained from a single eye lens. For assigning the isotopic trends observed in lens tissues to specific life stages or size classes, we established a relationship between lens size and fork length (FL) as a reference framework. The reconstructed nitrogen isotope chorology of chub mackerel showed an increase in trophic position of about 1 unit from juvenile (FL ∼30 mm) to adult stages (FL ∼300 mm). The variation in nitrogen isotope ratios of phenylalanine (a source amino acid) in the eye lenses was –3 to 5‰. This baseline variability could be used for estimating fish movements. This study proposed compound-specific nitrogen isotope analysis of amino acids in eye lenses as a new tool capable of reconstructing the geographic and trophic histories of migratory fish.